The submerged paradise. Childhood in the literature of Antón Castro - De Torres Olson, Graciela (Ondina - Ondine, 2022)
Antón Castro, as well as a renowned journalist (National Prize for Cultural Journalism 2013), is a careful poet and storyteller whose entire work is populated by the absences of his childhood, which he evokes especially in the pages of his books dedicated to children's and young people's literature, but also emerges in his adult literature: stories of flooded villages, relatives who left or loves abandoned to go to the big city. The characters' journeys always seem to follow the sentimental route of the author, moving away from his homeland or trying to return to it. In conclusion, Antón Castro turns his work into a constant comeback to the village of his childhood, with the intention of reliving the intensity of his first experiences and filling the voids by re-inhabiting his memories. Keywords: children's and youth literature, submerged village, lost childhood, migration, Antón Castro